1983
DOI: 10.1210/jcem-56-3-449
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Serum Thyrotropin (TSH) to the Thyroid Hormones after Oral TSH-Releasing Hormone in Patients with Preclinical Hypothyroidism*

Abstract: Serum thyroid hormone and TSH concentrations were measured before and after oral TRH (40 mg) administration in 46 women with preclinical hypothyroidism. Preclinical hypothyroidism was defined as serum T4 in the normal range, a normal or elevated basal serum TSH, and an exaggerated serum TSH response to TRH, in the absence of clinical manifestations of hypothyroidism. The results were compared to those in 22 normal women of the same age and body mass index. Overall, the patients had significantly lower mean val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
(19 reference statements)
2
19
0
Order By: Relevance
“…In fact, significant lowering of both FT4 and FT3 occurs in each of the three different grades of hypothyroid patients as classified according to Evered et al (1973), and is accompanied by a simultaneous significant in¬ crease in TSH secretion. These findings confirm and extend previous studies showing a gradual fall in T4 and a rise in TSH in similar groups of hypothyroids (Evered et al 1973;Sawin et al 1979;Bastenie et al 1980;Tunbridge et al 1981;Staub et al 1983). Significantly reduced FT3 levels in subclinical hypothyroidism were found in the present study as well as in that by Franklyn et al (1984a) despite normal T3 levels, as previously reported by others (Evered et al 1973;Sawin et al 1979;Bastenie et al 1980;Tunbridge et al 1981;Staub et al 1983).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, significant lowering of both FT4 and FT3 occurs in each of the three different grades of hypothyroid patients as classified according to Evered et al (1973), and is accompanied by a simultaneous significant in¬ crease in TSH secretion. These findings confirm and extend previous studies showing a gradual fall in T4 and a rise in TSH in similar groups of hypothyroids (Evered et al 1973;Sawin et al 1979;Bastenie et al 1980;Tunbridge et al 1981;Staub et al 1983). Significantly reduced FT3 levels in subclinical hypothyroidism were found in the present study as well as in that by Franklyn et al (1984a) despite normal T3 levels, as previously reported by others (Evered et al 1973;Sawin et al 1979;Bastenie et al 1980;Tunbridge et al 1981;Staub et al 1983).…”
Section: Discussionsupporting
confidence: 93%
“…Patients are usually classified as overt hypothyroid in the presence of typical symptoms and signs, low T4 and high TSH levels, mild hypothyroid when elevated TSH and low or normal T4 are associated with some clinical evi¬ dence of thyroid failure, and subclinically hypo¬ thyroid when TSH, basal and/or after TRH, is increased, T4 is in the normal range, and clinical manifestations of hypothyroidism are lacking (Evered et al 1973;Hall & Scanion 1979). Despite individual T4 levels in the normal range, patients with subclinical hypothyroidism have significantly lower mean serum T4 levels than healthy controls and subjects with asymptomatic autoimmune thy¬ roiditis and normal TSH secretion (Evered et al 1973;Sawin et al 1979;Bastenie et al 1980;Tunbridge et al 1981;Staub et al 1983). How¬ ever, serum free thyroid hormones (FT4, FT3) in hypothyroid patients have been evaluated in only a few investigations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these abnormalities appear to reflect what has become known as the "euthyroid sick syndrome" (21). A number of CTD patients had thyroid test values consistent with incipient or true biochemical primary hypothyroidism ( 3 1,32). However, a large number of the CTD patients had thyroid test values consistent with hyperthyroxinemid hypertriiodothyronemia (6).…”
Section: Prevalence Of Abnormal Thyroid Function Tests In Connective mentioning
confidence: 99%
“…Furthermore, human patients with preclinical hypothyroidism (serum T 4 normal, TSH normal or high, and exaggerated TRH response) often have low normal baseline T 4 concentrations but normal T 3 concentrations and therefore an increased T 3 :T 4 ratio. 32 The diagnostic applications of thyroid hormone levels in neonatal llamas are potentially significant. Congenital hypothyroidism has been reported in many species, 2,4,6,7,11,16,18,[21][22][23]29,34 and hypothyroidism in young llamas has also been reported.…”
Section: Discussionmentioning
confidence: 99%